Analisis Potensi Pemanfaatan Harta ‘Uqubat di Baitul Mal Aceh - Rachmad Riyanto; Ridwan Nurdin; Hendra Syahputra (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
This research investigates the effect of halal labeling and religiosity on purchasing decisions for beauty products, while also assessing the moderating role of gender in the relationship between these variables. The study utilized a sample of 100 cosmetic product users in Banda Aceh, selected through purposive sampling. Data were collected via an online questionnaire and analyzed using multiple linear regression and moderated regression analysis. The findings indicate that both halal labeling and religiosity significantly and positively influence purchasing decisions for cosmetic products. Consumers who place greater importance on halal labeling and exhibit higher levels of religiosity demonstrate a stronger tendency to purchase cosmetic products.